P.E.I A cruise towards the transforming future of the swans - Delgado, Liseth Johana; Nieves Quintero, Nidia Amparo; Sandoval Delgado, Luz Dary (Rastros Rostros, 2023)
The Ministry of National Education, through the General Law of Education and its regulatory decrees, has been consolidating the creation of the Institutional Educational Project - P.E.I. as a proposal whose main objective is to contribute to the improvement of the quality of life of our citizens. The work emphasizes values such as self-esteem, responsibility, autonomy, respect, tolerance and gender equity.